Justification of new equipment development for preparing concrete solutions (Academic journal Industrial Machine Building Civil Engineering, 2022)
Production of various types of reinforced concrete structures and concrete products of appropriate quality in Ukraine currently requires special attention, as there is an urgent need for rapid restoration and repair of buildings and structures after military operations. The preparation of concrete mixtures and mortars, as a rule, takes place at mechanized enterprises equipped with modern high-performance equipment, as well as directly on the construction site. The role of concrete mixing equipment in modern conditions is considered in the article. The need to develop a new design of small-sized mobile equipment for preparing concrete solutions was determined, and the existing mixing equipment was classified. On the basis of the conducted classification, the design features of the highly efficient equipment to be developed are determined
Keywords: сoncrete mixtures; concrete mixer; solution; preparation